High-valent iron (FeVI, FeV, and FeIV) species in water: characterization and oxidative transformation of estrogenic hormones. Issue 28 (27th June 2016) - Machalová Šišková, Karolína; Jančula, Daniel; Drahoš, Bohuslav; Machala, Libor; Babica, Pavel; Alonso, Paula Godoy; Trávníček, Zdeněk; Tuček, Jiří; Maršálek, Blahoslav; Sharma, Virender K.; Zbořil, Radek
Abstract : Transformation of estrogenic hormones using high-valent iron species is described. Abstract : This paper presents solid state synthesis and characterization of tetra-oxy iron(iv ) and iron(v ) species in their salt forms (Na4 FeO4 –Fe IV and K3 FeO4 –Fe V ). Stability of the synthesized salts, commonly called ferrates, in water was determined by applying the 57 Fe Mössbauer spectroscopy technique. Within 2 s in water, Fe IV converted into Fe III while Fe V transformed into Fe VI and Fe III at pH = 8.2. Comparatively, Fe VI (bought as K2 FeO4 ) remained stable in aqueous solution during the short time period. The oxidative removal efficiency of the high-valent iron species was then tested against five environmentally important estrogenic hormones (estron (E1), 17-β-estradiol (E2), estriol (E3), 17-α-ethinylestradiol (EE2), and diethylstibestrol (DES)) in effluent water of a wastewater treatment plant. Three dosages of iron species (1, 10, and 100 mg L −1 ) were applied to the effluent water. An increase in the concentration of dosages enhanced the removal of estrogens. Both Fe V and Fe VI were effective in degrading estrogens, but Fe IV showed limited oxidation capacity to transform estrogens. The oxidized products of the estrogens were analyzed using Raman spectroscopy and high-performance liquid chromatography-mass spectrometry (HPLC-MS) techniques. Results demonstrated the transformation of estrogens into low molecular weight oxygenated compounds such as quinone-like and opened-aromatic ring species. A detailed study on E1 by using excess Fe VI showed the mineralization of the parent compound. The results demonstrate great potential of high-valent iron species in the degradation of endocrine disruptor chemicals like estrogens with several superior aspects including fast reactions, complete degradation and/or formation of benign organic species, and environmentally-acceptable iron oxide by-products.